Implicit racism, colour blindness, and narrow definitions of discrimination: Why some White people prefer 'All Lives Matter' to 'Black Lives Matter'. (12th May 2021) - West, Keon; Greenland, Katy; van Laar, Colette
Abstract : The Black Lives Matter (BLM) movement has been called the 'civil rights issue of our time' (Holt & Sweitzer, 2020, Self and Identity, 19(, p. 16) but the All Lives Matter (ALM) movement swiftly emerged as an oppositional response to BLM. Prior research has investigated some predictors of support for ALM over BLM, but these predictors have thus far not included levels of racial bias or potentially relevant constructions of racism. This pre‐registered, cross‐sectional study ( N = 287) tested the degree to which White participants' support for ALM could be predicted using measures of racism (implicit and explicit) and ideological stances around the construction of 'racism' (that discourage the recognition of contemporary inequalities and discrimination). Using multiple regression analyses, we found that implicit racism, colour‐blind ideology, and narrow definitional boundaries of discrimination positively predicted support for ALM over BLM. Explicit racism, collective narcissism, and right‐wing political orientation did not predict ALM support, nor did any (2‐way) interaction of these predictors. Implications for our understanding of the All Lives Matter movement are discussed.